Strengthening of extra-tropical westerlies and formation of new wind maxima at 200 hPa over Indian region during winter and pre-monsoon seasons (MAUSAM, 1987)
There is a general strengthening of the extra-tropical westerlies in response to the organisation of strong convection in tropics. In the four case studies presented the formation of westerly wind maxima over a station at 200 hPa has been explained with the help of conservation of angular momentum when an air stream emerging from the top of the cloud acquires an additional westerly momentum during its northward motion. The air stream was identified by the continuity of outflowing cirrus cloud over the station. In such cases the westerlies extend deep into equatorial region and a double jet stream appears south of the main sub-tropical jet stream over Indian region. Further, westerlies are likely to be stronger during nights than during day time under the same forcing.The study conducted has shown that westerlies over the Indian region west of 80 deg. E strengthen in response to the intensification of convection in the equatorial trough over Arabian Sea.